A model for prediction of subsurface damage in rotary ultrasonic face milling of optical K9 glass. Issue 1 (March 2016) - Wang, Jianjian; Zhang, Chenglong; Feng, Pingfa; Zhang, Jianfu
Abstract Subsurface damage (SSD) induced by the rotary ultrasonic face machining (RUFM) considerably influences the technological application of the optical components. However, currently, there is no method to detect the depth of SSD in real time. For the purpose of precise and nondestructive evaluation of the SSD depth generated in RUFM processes, a predictive model was developed by applying the indentation fracture mechanics of brittle material. This was the first time that the correlation between the measured cutting force and SSD depth had been established. It was found that the SSD depth was directly proportional to the exponent of the measured cutting force (namelyd SSD  = γF c χ ). Using this model, the depth of SSD could be predicted rapidly and precisely in the RUFM of optical glass even in real time using the measuring cutting force. Subsequently, this method was verified by conducting RUFM tests on K9 glass specimens with Sauer Ultrasonic 50. Meanwhile, the cutting force and SSD depth were compared experimentally between RUFM and conventional grinding (CG) process, indicating that RUFM is a beneficial manufacturing method for optical glass with reduced cutting force and SSD depth.